Word Formation and Meanings of English Makeup Terms in Indonesian Local Makeup Brands - Al Qubro, Chadijah; Saehu, Andang; Ardiansyah, Erlan Aditya (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research was aimed at analyzing the various word formations, their processes, and the meanings associated with English makeup terms in local Indonesian makeup brands. This research used a descriptive qualitative approach. The researcher collected the data by selecting items from The Female Daily Award 2024 official website. The researcher employed Yule's (2020) theory for both morphology and semantics in this study. The data that contained word formation were collected and then analyzed based on the processes of how the words are formed and analyzed the meaning using all the data. The research findings indicate that Indonesian local makeup brands employ five distinct forms of word formation in their English makeup terminology. The research identified five types of word formation, which included compound, clipping, coinage, derivation, and multiple processes. Among those types, compound emerged as the most prevalent word formation.